Lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermal sensitive ceramic material as well as preparation method and application thereof

By developing the negative temperature coefficient thermosensitive ceramic material of lanthanum, neodymium zirconium tin-based oxide, the problems of aging and performance changes in traditional ceramic materials in high temperature environments are solved, and a high sensitivity and long-life temperature sensing function is achieved at temperatures of 1000℃ or above.

CN119707490APending Publication Date: 2025-03-28XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411941093.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional spinel-type negative temperature coefficient thermosensitive ceramics are not suitable for high temperature environments above 300℃ and cannot meet the application needs of 1000℃ or above.

Method used

A series of lanthanum, neodymium zirconium tin-based oxide negative temperature coefficient thermosensitive ceramic materials have been developed, with the chemical formula of (La1/3Nd1/3M1/3)2(Zr1/2Sn1/2)2O7, where M is Sm, Eu, Gd or Dy. The material is mixed and fired by mixing and sintering of lanthanum trioxide, neodymium trioxide, M oxide, tin oxide and zirconia in a chemical formula molar ratio, and has an ultra-wide applicable temperature zone of 400°C to 1200°C and excellent electrical stability.

Benefits of technology

This material has negative temperature coefficient characteristics in the range of 400℃ to 1200℃, and is suitable for inert oxygen-free atmosphere or vacuum environments up to 1200℃, and has high-sensitive, long-life and low-cost high-temperature temperature sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707490A_ABST
    Figure CN119707490A_ABST
Patent Text Reader

Abstract

The invention discloses a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermal sensitive ceramic material as well as a preparation method and application thereof, belongs to the field of high-temperature thermal sensitive sensors, and aims to solve the problems that the traditional spinel type negative temperature coefficient thermal sensitive ceramic is not suitable for a high-temperature environment of 300 DEG C or above; and the application requirement in a high-temperature environment of 1000 DEG C or above cannot be met. The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermal sensitive ceramic material can be obtained by mixing raw materials according to a stoichiometric ratio and then carrying out ball milling, drying, powder calcination, hydrostatic pressure forming and high-temperature sintering, the chemical formula of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermal sensitive ceramic material is (La1 / 3Nd1 / 3M1 / 3) 2 (Zr1 / 2Sn1 / 2) 2O7, and M is Sm, Eu, Gd or Dy. The electrical property parameters are as follows: the material constant B is equal to 10233-12071K, the rho 1200 DEG C is equal to 1.196 * 10 < 2 > omega.cm to 1.668 * 10 < 2 > omega.cm, and the material has excellent aging stability at high temperature (the resistance drift rate is less than 1.68% after the material is aged at 1200 DEG C for 500 hours). Meanwhile, the thermal sensitive ceramic material with the negative temperature coefficient also has good applicability in an oxygen-free inert atmosphere and a vacuum environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high-temperature thermistors, in particular to the field of negative temperature coefficient thermistor ceramic materials, specifically to a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material, and a preparation method and application thereof. Background Art

[0002] In recent years, with the technological upgrading of my country's metallurgy, special processing, automobile, aerospace and other industries, there is an urgent need for high-temperature temperature sensors with high sensitivity, long life and low cost at 1000℃ and above, in an inert oxygen-free atmosphere or vacuum environment. The key to improving sensor performance lies in the sensing material. At present, the most widely used high-temperature temperature sensors are thermocouples, platinum resistors and negative temperature coefficient thermistors. Among them, thermocouples can achieve temperature measurements of 1600℃ or even higher because they use expensive metals such as platinum rhodium, tungsten rhenium, etc. as sensing materials, but because of their small thermoelectric potential changes and the need for cold end compensation, they have low sensitivity and poor reproducibility. More importantly, this type of sensor strictly limits the use of the atmosphere environment. Compared with thermocouples, platinum resistors with precious metal platinum as sensing materials have high measurement accuracy, but their upper limit of applicable temperature is only 650℃. In addition, the sensing materials used for thermocouples and platinum resistors are rare and precious metals, which are expensive and require armor protection, and do not have cost advantages. Negative temperature coefficient thermistors have gained widespread attention due to their high sensitivity, fast response, simple structure and low cost.

[0003] Traditional negative temperature coefficient thermistors have been widely used in the manufacture of medium-to-normal temperature (-50 to 300°C) thermistors because their carrier activation energy is small and the subgroup elements such as Mn, Co, and Fe contained in them can produce continuous valence changes and polaron hopping conduction without too high a temperature. However, these thermistors will undergo cation redistribution at high temperatures, resulting in irreversible changes in resistance-temperature characteristics and severe aging, so they are not suitable for high temperature environments above 300°C. At the same time, the resistance characteristics of these thermistors will also be affected by the atmosphere in the use environment; current research has found that different atmospheres will have a significant and profound impact on the concentration of holes inside the ceramic material, which in turn causes the performance of thermistors in different atmospheres to show significant differences.

[0004] In recent years, lanthanum, neodymium, zirconium, tin-based oxide ceramics have received widespread attention due to their high melting point and good semiconductor properties at high temperatures. Studies have found that compared with other high-temperature thermistors, this type of material has excellent physical and chemical properties and phase structure stability, and can still maintain a high resistivity at high temperatures. At the same time, its structure can accommodate a variety of metal ions, covering lanthanides, alkali metals, alkaline earth metals, and some sub-group and main-group metal elements. The diverse ion selectivity of lanthanum, neodymium, zirconium, tin-based oxide ceramics allows it to be doped with different metal ions to achieve regulation of the electrical properties of the material. Summary of the invention

[0005] The purpose of the invention is to provide a series of lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic materials, preparation methods and applications thereof, in view of the problem that traditional spinel-type negative temperature coefficient thermistor ceramics are not suitable for high temperature environments above 300°C and cannot meet the application requirements of 1000°C and above. This application provides thermistor material support for the development of high-temperature temperature sensors that are highly sensitive, long-life and low-cost and can be used in an inert oxygen-free atmosphere or vacuum environment up to 1200°C. The lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material of this application has an ultra-wide applicable temperature range of 400°C to 1200°C and has excellent electrical stability at an upper limit temperature of 1200°C. Furthermore, the negative temperature coefficient thermistor ceramic material of this application is tested in an inert oxygen-free atmosphere or vacuum environment, and the material shows good stability, which provides strong support for its use in temperature measurement in an inert oxygen-free atmosphere or vacuum environment.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] Lanthanum neodymium zirconium tin based oxide negative temperature coefficient thermistor ceramic material, its chemical formula is (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7, wherein M is Sm, Eu, Gd or Dy.

[0008] The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material has a negative temperature coefficient characteristic within the range of 400° C. to 1200° C.

[0009] The applicable temperature range of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is 400° C. to 1200° C.

[0010] The electrical performance parameters of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material within the applicable temperature range are as follows: material constant B = 10233K ~ 12071K, ρ 1200℃ =1.196×10 2Ω·cm~1.668×10 2 Ω·cm.

[0011] The resistance drift rate of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is less than 1.68% after aging at 1200° C. for 500 hours.

[0012] The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is prepared by mixing and sintering raw materials of lanthanum trioxide, neodymium trioxide, oxide of M, tin oxide and zirconium oxide according to a chemical formula molar ratio; the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide.

[0013] The preparation method of the above-mentioned lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material is to use lanthanum trioxide, neodymium trioxide, M oxide, tin oxide and zirconium oxide as raw materials, grind and mix them according to the chemical formula molar ratio, and then sinter them by high-temperature solid phase method; the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide.

[0014] The steps include:

[0015] a. According to the molar ratio of La:Nd:M:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, respectively weigh lanthanum trioxide, neodymium trioxide, oxide of M, tin oxide and zirconium oxide, mix and grind to obtain initial powder; wherein M is Sm, Eu, Gd or Dy, and the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide;

[0016] b. calcining the initial powder obtained in step a, and grinding it into powder to obtain a precursor powder;

[0017] c. The precursor powder obtained in step b is compression molded to obtain a compression molded block; the obtained compression molded block is hydrostatically pressed to obtain a hydrostatically pressed block; the hydrostatically pressed block is sintered to obtain a lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material.

[0018] In the step a, the preparation process of the initial powder is as follows: lanthanum trioxide, neodymium trioxide, M oxide, tin oxide and zirconium oxide weighed according to the molar ratio of La:Nd:M:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2 are put into a mortar, ground, and then taken out and dried to obtain the initial powder.

[0019] In the step a, the grinding equipment is a mortar grinder.

[0020] In the step a, the grinding time is 8 to 10 hours; and the drying temperature is 50° C. to 150° C.

[0021] In the step b, the calcination temperature is 900° C. to 1000° C., and the calcination time is 2 to 5 hours.

[0022] In the step b, the initial powder obtained in the step a is placed in a zirconia crucible for calcination.

[0023] In the step b, the powder obtained after calcination is ground into powder, and the grinding time is 2 to 5 hours to obtain a precursor powder.

[0024] In the step b, the grinding equipment is a mortar grinder.

[0025] In step c, the precursor powder obtained in step b is pressed by a uniaxial hydraulic press at 8 kg / cm 2 ~12kg / cm 2 The mold is pressed under a pressure of to obtain a molded block.

[0026] In the step c, the compression molding time is 0.5 to 10 minutes.

[0027] In the step c, the obtained compression molded block is hydrostatically pressed at a pressure of 200 MPa to 300 MPa using a hydrostatic press to obtain a hydrostatically pressed block.

[0028] In the step c, the holding time of the hydrostatic pressure is 3 to 10 minutes.

[0029] In the step c, the sintering temperature is 1500° C. to 1600° C., and the sintering time is 8 to 12 hours.

[0030] The application of the above-mentioned lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material, the chemical formula of which is (La 1 / 3 Nd 1 / 3M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7, wherein M is Sm, Eu, Gd or Dy.

[0031] The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is used to prepare a high-temperature thermistor.

[0032] The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is used to prepare a negative temperature coefficient thermistor.

[0033] The lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is used to prepare a negative temperature coefficient thermistor for use in an inert oxygen-free atmosphere or a vacuum environment.

[0034] The inert oxygen-free atmosphere is a nitrogen atmosphere.

[0035] The vacuum degree of the vacuum environment is 10-3 Pa.

[0036] As mentioned above, in order to develop a high-temperature temperature sensor that can be used for temperature measurement in a high-temperature environment of 1000°C or above and has both high sensitivity, long life and low cost, this application proposes a series of lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic materials, their preparation methods and applications. The chemical formula of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (where M is Sm, Eu, Gd or Dy), the material system has a negative temperature coefficient characteristic within 400℃~1200℃, that is, it has an ultra-wide operating temperature range of 400℃~1200℃ and excellent aging stability. This series of negative temperature coefficient thermistor materials are made by mixing and sintering raw materials of lanthanum trioxide, neodymium trioxide, oxide of M, tin oxide and zirconium oxide according to the chemical formula molar ratio; the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide.

[0037] The inventors have found that lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) can maintain a high resistivity at high temperatures, and its maximum applicable temperature limit can reach 1200°C, and it can be applied to an ultra-wide applicable temperature range of 400°C to 1200°C. At the same time, due to its high B value and excellent negative temperature coefficient characteristics in the applicable temperature range, this series of materials also exhibits high sensitivity and excellent electrical stability. The relationship between the resistance drift rate and aging time of the prepared ceramic material at 1200°C was measured, and it was found that after aging for 500 hours, the resistance drift rate of this series of materials was less than 1.68%. The results show that the ceramic material of the present application can be used in a high temperature environment of up to 1200°C and is used to manufacture high-temperature temperature sensors with high sensitivity, long life and low cost.

[0038] In addition, the inventors exposed this series of ceramic materials to a nitrogen atmosphere or a vacuum environment, and measured the resistance values ​​at different temperatures in an ultra-wide applicable temperature range of 400°C to 1200°C. The electrical test results show that at the same temperature, the resistivity of this series of ceramic materials in a nitrogen atmosphere or a vacuum environment hardly changes. This proves that this series of materials can be used to manufacture high-temperature temperature sensors in a nitrogen atmosphere or a vacuum environment at a maximum temperature of 1200°C. Therefore, the lanthanum neodymium zirconium tin-based oxide negative temperature coefficient thermistor material (La 1 / 3 Nd1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) not only has excellent structural stability, but is also suitable for oxygen-free inert atmosphere and vacuum environment, effectively expanding the application scenarios of negative temperature coefficient sensors.

[0039] In summary, the present application provides a series of novel lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic materials having an ultra-wide operating temperature range of 400°C to 1200°C and excellent sensitivity and electrical stability at high temperatures, as well as their preparation methods and applications in the field of high-temperature sensors. The lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic materials of the present application use lanthanum trioxide, neodymium trioxide, oxide of M (the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide), tin oxide and zirconium oxide as raw materials, which are mixed according to the chemical formula molar ratio, and then subjected to grinding, drying, powder calcination, molding, hydrostatic pressing, and high-temperature sintering in sequence to obtain lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic materials (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy). Its electrical performance parameters are: material constant B = 10233K ~ 12071K, ρ 1200℃ =1.196×10 2 Ω·cm~1.668×10 2 Ω·cm, and the resistance drift rate after aging for 500 hours at 1200℃ is less than 1.68%. It can be seen that the lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material of the present invention is a high-temperature negative temperature coefficient thermistor ceramic material with a high operating temperature upper limit, an ultra-wide applicable temperature range, and excellent sensitivity and electrical stability at high temperatures. In addition, the lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material of the present application has almost no change in resistivity when it is in a nitrogen atmosphere or vacuum environment in a working temperature range of 400℃ to 1200℃ (this may be because this series of materials has a unique crystal structure and excellent chemical stability, so that the hole concentration inside it is extremely limited by the influence of the atmosphere), indicating that this series of ceramics has good applicability in an oxygen-free inert atmosphere and a vacuum environment, and provides a new choice for a new type of high-temperature negative temperature coefficient thermistor ceramic material with a high sensitivity and long life and a higher applicable temperature upper limit in an inert oxygen-free atmosphere or a vacuum environment.

[0040] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0041] (1) The thermosensitive material of the present invention (La 1 / 3Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) has NTC characteristics in the temperature range of 400℃~1200℃, with a wide test temperature range and a high upper limit of operating temperature;

[0042] (2) Thermosensitive material (La) of the present invention 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) is aged at 1200°C for 500 hours, and the resistance drift rate is less than 1.68%, showing excellent electrical stability at high temperature;

[0043] (3) The thermosensitive material of the present invention (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) has a material constant B value within the applicable temperature range of 10233K to 12071K, ensuring sensitivity at high temperatures;

[0044] (4) The thermosensitive material of the present invention (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistivity of )2O7 (M is Sm, Eu, Gd or Dy) does not change dramatically in a nitrogen atmosphere or a vacuum environment, ensuring good applicability in an oxygen-free inert atmosphere and a vacuum environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The present invention will now be described by way of example with reference to the accompanying drawings, in which:

[0046] Figure 1 for (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) ceramic material in nitrogen atmosphere and vacuum environment (vacuum degree is 10 -3 A comparison of the relationship between the measured resistance and temperature of the sample (Pa). DETAILED DESCRIPTION

[0047] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0048] Any feature disclosed in this specification, unless otherwise stated, can be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0049] Example 1

[0050] In this embodiment, the lanthanum neodymium zirconium tin based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Sm 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 preparation process is as follows.

[0051] a. According to the molar ratio of La:Nd:Sm:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, weigh the oxide powders of lanthanum trioxide, neodymium trioxide, samarium trioxide, tin oxide and zirconium oxide respectively, grind them in a mortar grinder for 8 hours, take them out and dry them at 50°C to obtain initial powders.

[0052] B. The precursor powder obtained in step a is calcined at 900° C. for 2 hours, and then placed in a mortar grinder for 2 hours and taken out to obtain the precursor powder.

[0053] C. The precursor powder obtained in step b was pressed by a uniaxial hydraulic press at 8 kg / cm 2 The molded block was subjected to hydrostatic pressure treatment and maintained at a pressure of 200 MPa for 3 minutes to obtain a hydrostatically pressed block. The hydrostatically pressed block was sintered at a temperature of 1500°C for 8 hours to obtain a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Sm 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7.

[0054] The obtained lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Sm 1 / 3 )2(Zr 1 / 2Sn 1 / 2)2O7 was tested for electrical properties. The resistance values ​​and logarithms of resistivity at different temperatures are shown in Tables 1 and 2. The electrical parameters of the material are: the material constant B value is 10233K, ρ 1200℃ =1.196×10 2 Ω·cm.

[0055] At the same time, the prepared (La 1 / 3 Nd 1 / 3 Sm 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistance drift rate of the )2O7 ceramic material after aging at 1200℃ for different times was measured. The final result of the test was that the resistance drift rate was 0.83% after aging at 1200℃ for 500 hours, as shown in Table 3.

[0056] Example 2

[0057] In this embodiment, the lanthanum neodymium zirconium tin based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Eu 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 preparation process is as follows.

[0058] a. According to the molar ratio of La:Nd:Eu:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, weigh the oxide powders of lanthanum trioxide, neodymium trioxide, europium trioxide, tin oxide and zirconium oxide respectively, grind them in a mortar grinder for 9 hours, take them out and dry them at 80°C to obtain initial powders.

[0059] B. The precursor powder obtained in step a is calcined at 950° C. for 3 hours, and then placed in a mortar grinder for 3 hours and taken out to obtain the precursor powder.

[0060] C. The precursor powder obtained in step b was pressed by a uniaxial hydraulic press at 10 kg / cm 2 The molded block was subjected to hydrostatic pressure treatment and maintained at a pressure of 250 MPa for 5 minutes to obtain a hydrostatically pressed block. The hydrostatically pressed block was sintered at a temperature of 1500°C for 10 hours to obtain a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Eu 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7.

[0061] The obtained lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La1 / 3 Nd 1 / 3 Eu 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 was tested for electrical properties. The resistance values ​​and logarithms of resistivity at different temperatures are shown in Tables 1 and 2. The electrical parameters of the material are: the material constant B value is 10554K, ρ 1200℃ =1.395×10 2 Ω·cm.

[0062] At the same time, the prepared (La 1 / 3 Nd 1 / 3 Eu 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistance drift rate of the )2O7 ceramic material after aging at 1200℃ for different times was measured. The final result of the test was that the resistance drift rate was 1.13% after aging at 1200℃ for 500 hours, as shown in Table 3.

[0063] Example 3

[0064] In this embodiment, the lanthanum neodymium zirconium tin based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 G 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 preparation process is as follows.

[0065] a. According to the molar ratio of La:Nd:Gd:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, weigh the oxide powders of lanthanum trioxide, neodymium trioxide, gadolinium trioxide, tin oxide and zirconium oxide respectively, grind them in a mortar grinder for 10 hours, take them out and dry them at 120°C to obtain initial powders.

[0066] B. The precursor powder obtained in step a is calcined at 1000° C. for 4 hours, and then placed in a mortar grinder for another 4 hours and taken out to obtain the precursor powder.

[0067] C. The precursor powder obtained in step b was pressed by a uniaxial hydraulic press at 12 kg / cm 2 The molded block was subjected to hydrostatic pressure treatment and maintained at a pressure of 300 MPa for 8 minutes to obtain a hydrostatically pressed block. The hydrostatically pressed block was sintered at a temperature of 1550°C for 12 hours to obtain a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 G 1 / 3 )2(Zr1 / 2 Sn 1 / 2 )2O7.

[0068] The obtained lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 G 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 was tested for electrical properties. The resistance values ​​and logarithms of resistivity at different temperatures are shown in Tables 1 and 2. The electrical parameters of the material are: the material constant B value is 11604K, ρ 1200℃ =1.514×10 2 Ω·cm.

[0069] At the same time, the prepared (La 1 / 3 Nd 1 / 3 G 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistance drift rate of the )2O7 ceramic material after aging at 1200℃ for different times was measured. The final result of the test was that the resistance drift rate was 1.40% after aging at 1200℃ for 500 hours, as shown in Table 3.

[0070] Example 4

[0071] In this embodiment, the lanthanum neodymium zirconium tin based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Dy 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 preparation process is as follows.

[0072] a. According to the molar ratio of La:Nd:Dy:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, weigh the oxide powders of lanthanum trioxide, neodymium trioxide, dysprosium trioxide, tin oxide and zirconium oxide respectively, grind them in a mortar grinder for 8 hours, take them out and dry them at 150°C to obtain initial powders.

[0073] B. The precursor powder obtained in step a is calcined at 1000° C. for 5 hours, and then placed in a mortar grinder for 5 hours and taken out to obtain the precursor powder.

[0074] C. The precursor powder obtained in step b was pressed by a uniaxial hydraulic press at 10 kg / cm 2The molded block was subjected to hydrostatic pressure treatment and maintained at a pressure of 300 MPa for 10 minutes to obtain a hydrostatically pressed block. The hydrostatically pressed block was sintered at a temperature of 1600°C for 12 hours to obtain a lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Dy 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7.

[0075] The obtained lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 Dy 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 was tested for electrical properties. The resistance values ​​and logarithms of resistivity at different temperatures are shown in Tables 1 and 2. The electrical parameters of the material are: the material constant B value is 12071K, ρ 1200℃ =1.668×10 2 Ω·cm.

[0076] At the same time, the prepared (La 1 / 3 Nd 1 / 3 Dy 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistance drift rate of the )2O7 ceramic material after aging at 1200℃ for different times was measured. The final result of the test was that the resistance drift rate was 1.68% after aging at 1200℃ for 500 hours, as shown in Table 3.

[0077] Example 5

[0078] The obtained lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) was tested for electrical properties and the resistance values ​​at different temperatures were measured, as shown in Table 3.

[0079] Subsequently, the series of materials were exposed to a high temperature tube furnace in a nitrogen atmosphere to measure the negative temperature coefficient of thermistor ceramic materials based on lanthanum-neodymium-zirconium-tin oxide (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2The resistance values ​​of )2O7 (M is Sm, Eu, Gd or Dy) at different temperatures are listed in Table 4. The series of materials were exposed to a vacuum environment (vacuum degree of 10 -3 The negative temperature coefficient thermistor material of lanthanum-neodymium-zirconium-tin based oxide (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 The resistance values ​​of )2O7 (M is Sm, Eu, Gd or Dy) at different temperatures are listed in Table 5.

[0080] The nitrogen atmosphere and vacuum environment (vacuum degree 10 -3 The negative temperature coefficient thermistor ceramic material (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) at different temperatures. The comparison results are as follows Figure 1 The test results show that the resistance-temperature relationship of this series of materials in nitrogen atmosphere and vacuum environment is highly consistent.

[0081] Furthermore, Table 1 gives (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) ceramic material resistance value (Ω) at different temperatures; Table 2 gives (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) ceramic materials at different temperatures; Table 3 gives the logarithm of the resistivity of (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) ceramic material after aging at 1200℃ for different time periods; Table 4 gives the resistance drift rate (%) of the ceramic material exposed to nitrogen atmosphere (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2)2O7 (M is Sm, Eu, Gd or Dy) ceramic material resistance value (Ω) at different temperatures; Table 5 shows the resistance value of the ceramic material exposed to vacuum environment (vacuum degree is 10 -3 Pa) 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7 (M is Sm, Eu, Gd or Dy) ceramic material resistance value (Ω) at different temperatures.

[0082]

[0083]

[0084]

[0085] The basic concepts have been described above. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of this specification. Although not explicitly stated here, those skilled in the art may make various modifications, improvements and corrections to this specification. Such modifications, improvements and corrections are suggested in this specification, so such modifications, improvements and corrections still belong to the spirit and scope of the exemplary embodiments of this specification.

[0086] In addition, unless explicitly stated in the claims, the order of the processing elements and sequences described in this specification, the use of alphanumeric characters, or the use of other names are not intended to limit the order of the processes and methods of this specification. Although the above disclosure discusses some invention embodiments that are currently considered useful through various examples, it should be understood that such details are only for illustrative purposes, and the attached claims are not limited to the disclosed embodiments. On the contrary, the claims are intended to cover all modifications and equivalent combinations that are consistent with the essence and scope of the embodiments of this specification.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The present invention extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.

Claims

1. Lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material, characterized in that: Its chemical formula is (La 1 / 3 Nd 1 / 3M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7, wherein M is Sm, Eu, Gd or Dy.

2. The thermosensitive ceramic material according to claim 1, characterized in that: The electrical performance parameters of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material within the applicable temperature range are as follows: material constant B = 10233K ~ 12071K, ρ 1200℃ =1.196×10 2 Ω·cm~1.668×10 2 Ω·cm.

3. The thermosensitive ceramic material according to claim 1 or 2, characterized in that: The resistance drift rate of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material is less than 1.68% after aging at 1200°C for 500 hours.

4. The method for preparing the thermosensitive ceramic material according to any one of claims 1 to 3, characterized in that: Lanthanum trioxide, neodymium trioxide, M oxide, tin oxide and zirconium oxide are used as raw materials, ground and mixed according to the chemical formula molar ratio, and then sintered by a high-temperature solid phase method; the M oxide is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide.

5. The preparation method according to claim 4, characterized in that: The steps include: a. According to the molar ratio of La:Nd:M:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2, weigh lanthanum trioxide, neodymium trioxide, oxide of M, tin oxide and zirconium oxide respectively, mix and grind to obtain initial powder; wherein M is Sm, Eu, Gd or Dy, and the oxide of M is samarium trioxide, europium trioxide, gadolinium trioxide or dysprosium trioxide; b. calcining the initial powder obtained in step a, and grinding it into powder to obtain a precursor powder; c. The precursor powder obtained in step b is compression molded to obtain a compression molded block; the obtained compression molded block is hydrostatically pressed to obtain a hydrostatically pressed block; the hydrostatically pressed block is sintered to obtain a lanthanum, neodymium, zirconium, tin-based oxide negative temperature coefficient thermistor ceramic material.

6. The preparation method according to claim 5, characterized in that: In the step a, the preparation process of the initial powder is as follows: lanthanum trioxide, neodymium trioxide, M oxide, tin oxide and zirconium oxide weighed according to the molar ratio of La:Nd:M:Sn:Zr=1 / 3:1 / 3:1 / 3:1 / 2:1 / 2 are put into a mortar, ground, and then taken out and dried to obtain the initial powder.

7. The preparation method according to any one of claims 5 to 6, characterized in that In the step b, the calcination temperature is 900° C. to 1000° C., and the calcination time is 2 to 5 hours.

8. The preparation method according to any one of claims 5 to 7, characterized in that In the step c, the obtained compression molded block is hydrostatically pressed at a pressure of 200 MPa to 300 MPa using a hydrostatic press to obtain a hydrostatically pressed block.

9. The preparation method according to claim 5, characterized in that: In the step c, the sintering temperature is 1500° C. to 1600° C., and the sintering time is 8 to 12 hours.

10. Application of the lanthanum-neodymium-zirconium-tin-based oxide negative temperature coefficient thermistor ceramic material according to any one of claims 1 to 3, characterized in that: Its chemical formula is (La 1 / 3 Nd 1 / 3 M 1 / 3 )2(Zr 1 / 2 Sn 1 / 2 )2O7, wherein M is Sm, Eu, Gd or Dy.

Citation Information

Patent Citations

  • Oxygen-insensitive negative temperature coefficient heat-sensitive material based on high-entropy rare earth zirconate

    CN115894029A

  • Oxygen-insensitive negative temperature coefficient heat-sensitive material based on high-entropy rare earth stannate

    CN116023140A